The experience of stereotactic aspiration in treatment of brain abscesses - Zinkevych, Iaroslav; Kostiuk, Kostyantyn; Glavatskyi, Oleksandr; Bolіukh Andrii; Malysheva, Tatyana; Tkachik, Irina; Tsymbaliuk, Vitaliy (Ukrainian Neurosurgical Journal, 2015)
Purpose. To estimate efficiency of stereotactic aspiration of intracerebral abscesses in deep and functionally eloquent brain areas. Methods. 12 patients with brain abscesses who underwent stereotactic aspiration were included into the study. Stereotactic interventions were performed using CRW Radionics Stereotactic System with StereoFusion, StereoPlan (Radionics) and FraimLink (Medtronic) software for target definition. Postoperative follow-up was from 1 to 36 months, in average (14±3.6) months. Results. During surgery in 11 (91.7%) patients pus was evacuated from abscess cavity, in 1 (8.3%) — late cerebritis was defined. There were no complications, all patients are alive. 3 months after surgery neurological symptoms regressed in 9 (75%) patients, in 2 (16.7%) — permanent neurological deficit preserved. Conclusions. Stereotactic aspiration is an effective and safe method of surgical treatment of brain abscesses. It could be the therapy of choice over open surgery because it is less invasive, thus reducing likelihood of neurological complications.